PENGARUH FAKTOR SOSIAL TERHADAP PRESTASI KERJA KARYAWAN PADA AKADEMI MARITIM YOGYAKARTA (AMY) - Suyanti Suyanti (Majalah Ilmiah Bahari Jogja, 2017)
This study examines the influence of social faktors on employeeperformance at the Yogyakarta Maritime Academy (AMY). The problemstudied is the influence of social faktors on employee performance.This research is a quantitative research that uses primary dataas its data source. Data were obtained from questionnaires toemployees of the Yogyakarta Maritime Academy. Data were analyzedusing simple linear regression.The result of the research concludes that there is a significantinfluence of social faktors on employee performance at the YogyakartaMaritime Academy (AMY). It can be known from simple linearregression test that get significance level (Sig) < 0,05. The greatinfluence given by social faktors on work performance is equal to 0.811 (80.11%). This means that every 10% increase of social faktorswill increase 80.11% employee performance.Keywords: Social Faktors, Employee Performance